Pijat Oksitosin sebagai Upaya Dalam Peningkatan Produksi ASI di RSUD DR. H. Jusuf SK Tarakan - Eni Tri Sudarman; Moneca Diah Listiyaningsih; Kurniawati; Gresloan, Anny; Damayanty, Thisna (Universitas Ngudi Waluyo, 2024)
Breastfeeding is the best method to increase life expectancy for a baby. However, coverage of exclusive breastfeeding in the first six months of a baby's life is still quite low at RSUD Dr. H. Jusuf Sk Tarakan. Even though breastfeeding is a natural activity, there are many obstacles. Starting from physiological and psychological conditions. Of the several obstacles in breastfeeding, the majority of people complaining about producing little breast milk is a complaint. There are several solutions to overcome complaints and obstacles to producing little breast milk. One method that can be applied is through oxytocin massage. Oxytocin massage applied to breastfeeding mothers can increase the amount of breast milk on the third day after birth. Apart from that, oxytocin massage also speeds up the production phase of the breastfeeding hormone, the hormone prolactin so that breast milk supply increases gradually. So, community service activities (PkM) were carried out to provide knowledge about oxytocin massage and train how to do oxytocin massage to the husbands or families of postpartum patients at RSUD Dr. H. Jusuf Sk Tarakan Oxytocin massage training was carried out on 20 postpartum and breastfeeding patients. The activities provided included the delivery of material on oxytocin massage techniques through leaflets, lectures, as well as a simulation of oxytocin massage skills which was held in the Dr. RSUD Hall. H. Jusuf Sk Tarakan. The planned output target of this PKM activity is the publication of articles in the CFP Midwifery Study Program. The results of this PkM activity show a gradual increase in knowledge and skills of the target in carrying out oxytocin massage, with an increase in knowledge of 40%. It is recommended that midwives teach the oxytocin massage technique to every postpartum mother and make it a routine part of postpartum mother's care to help increase breast milk production. Abstrak Menyusui merupakan metode terbaik untuk meningkatkan angka harapan hidup bagi seorang bayi. Namun, cakupan pemberian ASI ekslusif pada enam bulan pertama kehidupan bayi masih cukup rendah di RSUD Dr. H. Jusuf Sk Tarakan. Walaupun menyusui merupakan kegiatan yang bersifat alamiah, namun ada banyak kendala. Mulai dari kondisi yang bersifat fisiologis maupun psikologis. Dari beberapa kendala dalam menyusui, pengeluaran ASI yang sedikit mayoritas menjadi keluhan. Terdapat beberapa solusi untuk mengatasi adanya keluhan dan kendala pengeluaran ASI yang sedikit. Salah satu metode yang bisa diterapkan adalah melalui pijat oksitosin. Pijat oksitosin yang diterapkan pada ibu menyusui mampu memperbanyak jumlah ASI pada hari ketiga pasca kelahiran. Selain itu, pijat oksitosin juga mempercepat fase produksi hormon menyusui, hormon prolaktin sehingga suplai ASI meningkat secara bertahap. Maka, kegiatan pengabdian kepada masyarakat (PkM) dilakukan untuk memberikan pengetahuan tentang pijat oksitosin dan melatih cara melakukan pijat oksitosin pada suami atau keluarga pasien nifas di RSUD Dr. H. Jusuf Sk Tarakan Pelatihan pijat oksitosin dilakukan pada 18 pasien nifas dan menyusui. Kegiatan yang diberikan meliputi penyampaian materi tentang teknik pijat oksitosin melaui media leaflet, dan ceramah, serta simulasi keterampilan pijat oksitosin yang diadakan di Aula RSUD Dr. H. Jusuf Sk Tarakan.Target luaran yang direncanakan dari kegiatan PKM ini adalah meningkatkan pengetahuan ibu tentang pijat oksitosin. Hasil dari kegiatan PkM ini menunjukkan adanya peningkatan pengetahuan secara bertahap dan keterampilan pada sasaran dalam melakukan pijat oksitosin, dengan peningkatan pengetahuan sebesar 40%. Disarankan agar bidan mengajarkan teknik pijat oksitosin kepada setiap ibu nifas dan menjadikannya sebagai bagian rutin dari perawatan ibu nifas untuk membantu meningkatkan produksi ASI.